Strategi Pemasaran Sosial Yayasan Setara Melalui Aktivasi Media Sosial, Sosialisasi Orang Tua, Rekrutmen Relawan, Main Event, Dan Pendampingan Anak - Krista Adelia Mawar Sari; Joyo Nur Suryanto Gono (Interaksi Online, 2026)
Child protection issues in Indonesia remain a serious challenge, particularly related to the low level of public awareness regarding the importance of protecting and fulfilling children's rights. Yayasan Setara, as a Non-Governmental Organization (NGO) focusing on child protection and welfare in Semarang City, seeks to increase organizational visibility and encourage community involvement through various social programs. However, based on the results of the audience research conducted, the level of public awareness of Yayasan Setara is still relatively low. Therefore, a more targeted communication strategy is needed to increase brand awareness while also encouraging community participation in Yayasan Setara’s programs. This professional project report discusses the implementation of Yayasan Setara’s social marketing program designed to increase organizational visibility and expand the reach of child protection messages to the community. The program consists of three main activities, namely optimizing Instagram (@yayasansetara) and TikTok (@yayasansetarasmg) social media platforms, increasing brand awareness through socialization activities with parents, roadshows to stakeholders, and the distribution of educational posters, as well as community participation programs through open volunteer recruitment, child mentoring activities, community roadshows, and the organization of the Setara Youth Movement main event. In the implementation of these programs, the author served as Design & Creative and Content Planner responsible for content planning, message development, visual material production, and managing content distribution on Yayasan Setara’s social media platforms. The communication strategy used in this program refers to the concept of Integrated Marketing Communication (IMC), which emphasizes the integration of various communication media so that the messages delivered can be consistently received by the target audience. The results of the program implementation show an increase in the visibility and engagement of audiences with Yayasan Setara, both through the growth of social media reach, digital interactions, and community participation in various activities organized. Therefore, the implementation of an integrated social marketing communication strategy can contribute to increasing public awareness of Yayasan Setara and encourage public participation in supporting child protection and welfare efforts in Semarang City.